The Photographic history of the Civil War, volume 4 : soldier life and secret service. Prisons and hospitals. (Secaucus, NJ : Blue & Grey Press, 1987)
Presents various aspects of life in the Union and Confederate armies, in their secret services, and in prisons and hospitals
Reprint. Originally published as v.7 and v.8 of: The photographic history of the Civil War / Francis Trevelyan Miller, editor-in-chief ; Robert S. Lanier, managing editor. 1912, c1911.
Keywords: United States -- History -- Civil War, 1861-1865.; United States. -- Army -- History -- Civil War, 1861-1865.; Confederate States of America. -- Army -- History; United States -- History -- Civil War, 1861-1865 -- Secret service; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Civil War, 1861-1865 -- Hospitals; United States. -- Army -- Military life; Confederate States of America. -- Army -- Military life; United States -- History -- 1861-1865, Civil War